Expectations of Individuals with Neurological Conditions from Rehabilitation: A Mixed-Method Study of Needs (2021)
Background: Knowledge of the specific expectations of patients with neurological conditions (NCs) from rehabilitation helps in setting attainable goals. Such expectations may vary from situation to situation. There are no studies investigating rehabilitation expectations amongst individuals with NCs in Nigeria. Objectives: The aim of our study was to explore the rehabilitation expectations of individuals with NCs. Method: This convergent mixed-methods study comprised a cross-sectional survey of 105 individuals with NCs and two sessions of Focus Group Discussions (FGDS) amongst eight individuals with NCs. The modified Needs Assessment Questionnaire was used to assess rehabilitation needs as a proxy for rehabilitation expectations, whilst disability was assessed using the World Health Organization Disability Assessment Schedule 2.0. Quantitative data were summarised using descriptive statistics and analysed using inferential statistics at p < 0.05. Thematic analysis was conducted on the qualitative data. Results: Sixty-one (58.1%) stroke survivors, 33 (31.4%) individuals with spinal cord injury (SCI) and 11 (10.5%) with traumatic brain injury (TBI) aged 46.48 ± 15.91 were surveyed. The need for social/recreational activity was the most expressed need (100%) amongst the participants. Mobility was reported as an important need constituting a barrier to enjoying life by 93 (88.6%) participants. Individuals with SCI expressed the greatest needs compared with the other two groups. Needs were significantly correlated with severity of disability (p < 0.05). Four overarching themes (physical health, financial, healthcare services/rehabilitation and emotional/social) representing major areas of needs emerged from the FGD data. Conclusion: Individuals with NCs in Nigeria have specified expectations of rehabilitation. Disability was a major driver of these expectations, irrespective of NC subtype. Clinical implications: Rehabilitation programmes for individuals with NCs should target expressed needs or expectations of each patient cohort and minimise disabilities associated with these conditions.